AN ANALYSIS OF STUDENTS’ SKILL IN APPLYING THE PROBLEM SOLVING STRATEGY TO THE PHYSICS PROBLEM SETTLEMENT IN FACING AEC AS GLOBAL COMPETITION (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2016)
The results of previous studies show that students of Physics Education (S1 and S2), FKIP Syiah Kuala University more than 50% do not understand the programs and roadmap of Pilar ASEAN Socio-Cultural Community as a part of the ASEAN Economic Community (AEC). The inference of those results to the implementation of learning physics and science education system needs to be implemented through a link and match learning model that can improve the ability to think critically and creatively, and students need to be trained to be problem solvers, not the problem makers.Based on these problems, through this research has been applied physics learning by using Problem Solving strategies on 25 students of Master of Physical Education and Science. At the end of the implementation study measured the ability of students to apply problem-solving strategies in accordance with Answer Sections of Problem Solving adopted from previous research. The results showed that the majority of students (78%) are able to implement the stage I (Focus on Problem) with a complete, almost all respondents (91%) was only able to implement the stage II (Describe the Physics) of about 40%, almost all respondents (91% ) can apply for the stage III (Plan The Solution) approximately 80% of all respondents have been able to implement the stage IV (Excute the Plan) perfectly, and all respondents have been able to apply the stage V (Evaluate the Answer) completely. It is expected that all staff of teaching Science materials (Physics), they are recommended strongly to implement Problem Solving as an alternative strategy for preparing students to face global competition in the ASEAN Economic Community (AEC).